Customized microporous hard carbon negative electrode material and preparation method and application thereof

By evaporating the hard carbon precursor material containing heteroatoms at high temperature, a high specific surface area and rich microporous microporous hard carbon material was prepared, which solved the problem of the rate performance of the negative electrode material of sodium ion battery and the low efficiency of the first Coulomb, and achieved efficient Electrochemical properties and good cycle stability.

CN119461323AActive Publication Date: 2025-02-18GUANGDONG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411638232.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-02-18
Estimated Expiration
2044-11-16

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode hard carbon material has poor performance, low efficiency for the first time, and the battery has a large loss of irreversible capacity.

Method used

By evaporating with high temperature of hard carbon precursor materials containing heteroatoms, a microporous hard carbon material with high specific surface area and rich micropores was prepared, breaking the view that high specific surface area leads to low first-time Coulomb efficiency.

Benefits of technology

It achieves high first-time Coulomb efficiency and magnification capabilities, has good cycle stability, and the process can adjust the specific surface area and pore size according to requirements, which is suitable for more fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461323A_ABST
    Figure CN119461323A_ABST
Patent Text Reader

Abstract

The invention discloses a customized microporous hard carbon negative electrode material as well as a preparation method and application thereof, and belongs to the technical field of electrochemical energy storage materials. The preparation method comprises the following steps: S01, flatly laying a deposition substrate in a reactor, then placing the reactor in a deposition device, introducing a reactant for reaction, and cooling to room temperature after the reaction is finished to obtain an initial sample; s02, taking out the initial sample obtained in the step S01, and adding a solvent into the initial sample for soaking; and after soaking is completed, carrying out suction filtration, drying, heating and cooling to obtain the customized microporous hard carbon negative electrode material. The customized micropore hard carbon negative electrode material is large in specific surface area, has abundant open micropores lower than 1nm, and is beneficial to improving the first coulombic efficiency of a sodium ion battery; meanwhile, the micropores adsorb sodium ions to generate more capacity, the electrochemical performance is high, and the rate capability is excellent; the problems of high specific surface area and low first coulombic efficiency in the prior art are solved, and the cycling stability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to a customized microporous hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] In order to vigorously develop sustainable energy, large-scale energy storage technology has received enough attention. However, the development of lithium-ion batteries, which are widely used today, is restricted by the uneven distribution of lithium resources and international political issues. In comparison, sodium-ion batteries are expected to become the most attractive alternative.

[0003] First of all, sodium and lithium belong to the same main group and have similar chemical properties. However, the abundance of sodium in the earth's crust (2.74%) is much higher than that of lithium (0.0065%), so sodium batteries are cheaper to develop commercially. In terms of safety, lithium-ion batteries are prone to produce dendrites at high current densities, and may even pierce the diaphragm and cause a short circuit. In comparison, sodium batteries have a low probability of producing dendrites and are safer.

[0004] At present, the negative electrode materials of sodium ion batteries can be divided into the following categories: alloy materials, conversion materials, titanium-based materials and carbon-based materials. Among them, hard carbon materials have good conductivity, no obvious volume expansion, good cycle stability, and easier to obtain precursors; however, hard carbon materials generally have poor rate performance and low first coulomb efficiency, that is, the irreversible capacity loss of the battery is greater.

[0005] The problem of low rate and first coulombic efficiency of batteries can be effectively solved by adjusting the structure of hard carbon materials (introducing micropores). Considering that the increase of material specific surface area will increase the irreversible capacity, many scholars are more focused on manufacturing closed micropores of materials to improve the first coulombic efficiency of materials. In fact, microporous materials with large specific surface area are generated in the form of open pores, which can also bring about the improvement of first coulombic efficiency and the increase of rate performance. Summary of the invention

[0006] Based on this, the embodiments of the present invention provide a customized microporous hard carbon negative electrode material and its preparation method and application. It aims to solve the problems of poor rate performance, low first coulombic efficiency and large irreversible capacity loss of the battery in the existing hard carbon materials for the negative electrode of sodium ion batteries. The preparation method of the present invention obtains microporous hard carbon with high specific surface area, rich micropores and excellent electrochemical performance by high-temperature evaporation of hard carbon precursor materials containing heteroatoms, breaking the previous view that high specific surface area leads to low first coulombic efficiency, and has high first coulombic efficiency and rate capability, as well as good cycle stability; and in terms of process, it can customize the production of microporous hard carbon materials with specific specific surface area and pore size by changing the elements and content according to different needs, and is expected to be applied in more fields.

[0007] The technical solution of the present invention is achieved in this way:

[0008] A method for preparing a customized microporous hard carbon negative electrode material comprises the following steps:

[0009] S01, laying the deposition substrate flat in the reactor, then placing the reactor in a deposition device, introducing the reactants to react, and cooling to room temperature after the reaction is completed to obtain an initial sample;

[0010] S02, taking out the initial sample obtained in step S01, adding a solvent to the initial sample for soaking; after the soaking is completed, filtering, drying, heating, and cooling to obtain a customized microporous hard carbon negative electrode material.

[0011] As a preferred embodiment, in step S01,

[0012] The deposition substrate is freeze-dried sodium chloride powder.

[0013] The amount of the deposition substrate is 10 g to 15 g.

[0014] The reactant is at least one of carbon disulfide, phosphorus trichloride, selenium chloride or hydroiodic acid.

[0015] When the reactant is carbon disulfide, there is no need to add a gas containing carbon elements;

[0016] When the reactant is at least one of phosphorus trichloride, selenium chloride or hydroiodic acid, it is necessary to add a gas containing carbon elements.

[0017] The dosage of the reactant is 10-15 ml.

[0018] The carbon-containing gas is preferably a hydrogen mixed gas with a methane volume content of 30%, and a flow rate of 50 sccm to 150 sccm.

[0019] The reactor is a corundum ark; the deposition device is a plasma enhanced chemical vapor deposition device.

[0020] The initial temperature of the reaction is 20°C to 50°C, the reaction temperature of the reaction is 20°C to 500°C, the heating rate is 10°C / min; the reaction time is 30min to 60min.

[0021] The cooling method is to remove the heating component of the deposition device after the reaction is completed, so that the sample can be quickly cooled down to room temperature.

[0022] As a preferred embodiment, in step S02,

[0023] The solvent is deionized water. The amount of the solvent used is 50 ml to 100 ml. The deposited substrate can be removed by soaking in the solvent.

[0024] The soaking time is 8 to 12 hours. The soaking is preferably carried out in a beaker.

[0025] The number of times of the suction filtration is 1 to 2 times.

[0026] The drying temperature is 50°C to 100°C, and the drying time is 10h to 12h. Further preferably, the drying is preferably carried out in an electric heated blast drying oven.

[0027] The heating device for heating is preferably a tubular furnace.

[0028] The heating temperature is 900° C. to 1000° C., the heating time is 30 min to 90 min, and the heating atmosphere is nitrogen; the heteroatoms of the initial sample are evaporated by heating.

[0029] A customized microporous hard carbon negative electrode material is obtained by the above preparation method.

[0030] The above customized microporous hard carbon negative electrode material is used in sodium ion batteries.

[0031] In the present invention, the prepared customized microporous hard carbon negative electrode material has a pore size of less than 1nm, and the rich microporous structure can effectively prevent a large number of solvent molecules from entering the material during the charge and discharge process, thereby reducing the irreversible capacity loss caused by the decomposition of solvent molecules, limiting the formation of the solid electrolyte surface in the pore, and improving the first coulombic efficiency. In addition, sodium ions can migrate freely in the pores, and the active sites on the surface of the pores can remain stable in long cycles because there is no interference from solvent molecules, which is conducive to improving the rate and long cycle capacity of the material.

[0032] In addition, hard carbon precursors containing heteroatoms (S, P, Se, I) can be obtained quickly and at low cost through plasma chemical vapor deposition technology, and the heteroatomic molecules will not undergo large-scale agglomeration. Depending on the different heteroatom elements and the difference in the elemental content of heteroatoms in the precursor, simply heating the hard carbon precursor at high temperature can directly obtain a large-area microporous material suitable for use as a negative electrode material for sodium ion batteries. This is because the heteroatoms will leave micropores similar to the size of the molecules after volatilization at high temperatures. The entire process is efficient and simple, and can be commercialized for large-scale production.

[0033] In addition, due to the differences in heteroatom elements and the changes in the heteroatom content in the precursor under different experimental conditions, the specific surface area and pore size of the hard carbon material formed are quite different. Therefore, hard carbon can be customized according to different needs, that is, the heteroatom elements and content can be adjusted to specifically manufacture porous hard carbon materials with specific surface area and pore size limited to a certain range. The entire process is efficient and simple, and can be commercialized for large-scale production.

[0034] Compared with the prior art, this application has the following technical effects:

[0035] The customized microporous hard carbon negative electrode material obtained by plasma vapor evaporation deposition and high-temperature heating in the present application has a high specific surface area and rich microporous structure. A large number of microporous structures are conducive to the desolvation of solvated sodium ions during the cycle, which improves the first coulombic efficiency. At the same time, the defects and active sites in the micropores promote the transmission of sodium ions and enhance the rate performance. The sheet structures with high specific surface areas are stacked on each other, which reduces the volume expansion of the material and forms a sodium ion channel with high conductivity. In addition, in terms of process, it is only necessary to change the experimental conditions to customize hard carbon with different specific surface areas and pore sizes. The customization idea is simple and efficient. The preparation method of the present application is simple, low-cost, and can be suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 BET characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 1 of the present invention;

[0038] Figure 2 XRD characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 1 of the present invention;

[0039] Figure 3 This is a SEM characterization image of the customized microporous hard carbon negative electrode material for sodium ion batteries prepared in Example 1 of the present invention;

[0040] Figure 4 TEM characterization image of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 1 of the present invention;

[0041] Figure 5 A half-cell rate performance test diagram of the assembled microporous hard carbon negative electrode material customized for the sodium ion battery prepared in Example 1 of the present invention;

[0042] Figure 6 A test diagram of the cycle performance of a half-cell assembled with the sodium ion customized microporous hard carbon negative electrode material prepared in Example 1 of the present invention at a current density of 50Ag-1;

[0043] Figure 7 BET characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 2 of the present invention;

[0044] Figure 8 XRD characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 2 of the present invention;

[0045] Fig. 9 A test diagram of the cycle performance of a half-cell assembled with the sodium ion customized microporous hard carbon negative electrode material prepared in Example 2 of the present invention at a current density of 500 mA g-1;

[0046] Fig.10 BET characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 3 of the present invention;

[0047] Fig.11 BET characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 4 of the present invention.

[0048] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0051] At present, most hard carbon negative electrode materials for sodium ion batteries have low specific surface areas. The traditional view is that a large specific surface area will cause a large irreversible capacity loss because more solid electrolyte interfaces (SEI) will form on its surface. However, customized microporous materials break the traditional view. They have a large specific surface area within the micropores and abundant ultra-micropores. The micropores prevent a large number of free solvent molecules from entering the material, promote desolvation, and improve the first coulombic efficiency. At the same time, the micropores will also adsorb a large number of sodium ions, providing a high adsorption capacity during the cycle and enhancing the electrochemical performance.

[0052] Example 1

[0053] A method for preparing a customized microporous hard carbon negative electrode material (carbon disulfide reactant) comprises the following steps:

[0054] S01. Spread 15g of freeze-dried sodium chloride powder (deposition substrate) in a corundum ark reactor, then place the corundum ark reactor in a plasma enhanced chemical vapor deposition device, and introduce 15ml of carbon disulfide for reaction. The initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 40°C, the heating rate is 10°C / min, and the reaction time is 60min. After the reaction is completed, remove the heating component of the deposition device, and let the sample cool down quickly to room temperature to obtain an initial sample.

[0055] S02. Take out the initial sample in step S01 into a beaker, and add 100 ml of deionized water to the initial sample for soaking for 8 hours; after soaking, filter twice, dry in an electric blast drying oven at 50°C for 10 hours, and then heat in a tubular furnace. The atmosphere of the tubular furnace is nitrogen, the heating time is 60 minutes, the heating temperature is 1000°C, and after cooling, a customized microporous hard carbon negative electrode material is obtained.

[0056] The customized microporous hard carbon negative electrode material prepared in Example 1 was used as the active material; the active material, conductive carbon black, and polyacrylic acid were weighed in a mortar according to a mass ratio of active material: conductive agent: binder = 6:3:1, ground and mixed evenly, NMP solution was added and mixed evenly to a paste slurry, and then coated on a conductive copper foil, and the copper foil containing the active material dried at 80°C for 12h was used as the negative electrode, and the sodium sheet was used as the counter electrode; sodium hexafluorophosphate NaPF6 was used as the solute, and ethylene glycol dimethyl ether DME was used as the solvent, and the concentration was prepared to be 1 mol.L -1 solution as the electrolyte; finally, a 2032 button-type sodium ion half-cell was assembled and a charge and discharge test was performed, with a test voltage window of 0.01V-2.7V.

[0057] The BET characterization diagram of the customized microporous hard carbon negative electrode material provided in Example 1 is as follows Figure 1 shown; from Figure 1 It can be observed that the microporous hard carbon material has micropores of 0.64 nm and a large specific surface area of ​​1252 m 2 g -1 .

[0058] The XRD characterization diagram of the customized microporous hard carbon negative electrode material prepared in Example 1 is as follows Figure 2 As shown, from Figure 2 It can be found that the structure of the customized microporous hard carbon negative electrode material prepared in this embodiment is an amorphous carbon peak package.

[0059] The SEM characterization image of the customized microporous hard carbon negative electrode material prepared in Example 1 is as follows Figure 3 As shown, from Figure 3 It can be seen that the microporous hard carbon negative electrode material prepared in this embodiment is a sheet-like porous carbon.

[0060] The TEM characterization image of the customized microporous hard carbon negative electrode material prepared in Example 1 is as follows Figure 4 As shown, from Figure 4 It can be seen that the microporous hard carbon negative electrode material prepared in this embodiment is a porous carbon material with a uniformly distributed carbon layer.

[0061] The half-cell rate performance test diagram of the customized microporous hard carbon negative electrode material assembled in Example 1 is shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the current density is 0.2A·g -1 ~30A·g -1 The range of the electrode increases step by step, with the electrode at 0.2, 0.5, 1, 2, 5, 10, 15, 20, 30 A g -1 The average capacities were 502, 459, 427, 408, 392, 376, 362, 357, and 345 mAh g -1 When the current density returns to 0.2A·g -1 When the capacity is still up to 500Ah·g -1 , showing good rate performance.

[0062] The customized microporous hard carbon negative electrode material prepared in Example 1 is applied to sodium ion batteries. The half-cell assembled with the microporous hard carbon negative electrode material for sodium ion batteries prepared in Example 1 is subjected to a 50A·g -1 The cycle performance test diagram at the current density is as follows Figure 6 As shown, from Figure 6 It can be seen that at 50A·g -1 After 6000 cycles at a current density of 260 mAh g -1 The capacity shows good cycle stability.

[0063] Example 2

[0064] A method for preparing a customized microporous hard carbon negative electrode material (phosphorus chloride reactant) comprises the following steps:

[0065] S01. Spread 15g of freeze-dried sodium chloride powder (deposition substrate) in a corundum ark reactor, then place the corundum ark reactor in a plasma enhanced chemical vapor deposition device, introduce phosphorus trichloride and carbon-containing gas for reaction, the amount of phosphorus trichloride is 15ml, the initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 500°C, the heating rate is 10°C / min, and the reaction time is 60min; after the reaction is completed, remove the heating component of the deposition device, and let the sample cool down quickly to room temperature to obtain an initial sample;

[0066] The carbon-containing gas is a hydrogen mixed gas with a flow rate of 150 sccm and a methane volume content of 30%;

[0067] S02. Take out the initial sample in step S01 into a beaker, and add 100 ml of deionized water to the initial sample for soaking for 8 hours; after soaking, filter twice, dry in an electric blast drying oven at 50°C for 10 hours, and then heat in a tubular furnace. The atmosphere of the tubular furnace is nitrogen, the heating time is 60 minutes, the heating temperature is 1000°C, and after cooling, a customized microporous hard carbon negative electrode material is obtained.

[0068] The customized material prepared in Example 2 was used as the active material. The active material, conductive carbon black, and polyacrylic acid were weighed in a mortar according to a mass ratio of active material: conductive agent: binder = 6:3:1, and ground and mixed evenly. NMP solution was added and mixed evenly to a paste slurry, which was then applied to a conductive copper foil. The copper foil containing the active material dried at 80°C for 12h was used as the negative electrode, and the sodium sheet was used as the counter electrode. Sodium hexafluorophosphate NaPF6 was used as the solute, and ethylene glycol dimethyl ether DME was used as the solvent. The concentration was prepared to be 1 mol·L -1 solution as the electrolyte; finally, a 2032 button-type sodium ion half-cell was assembled and a charge and discharge test was performed, with a test voltage window of 0.01V-2.7V.

[0069] The BET characterization diagram of the customized microporous hard carbon negative electrode material provided in Example 2 is as follows Figure 7 shown; from Figure 7 It can be observed that the customized microporous hard carbon electrode material has micropores of 0.73 nm and a large specific surface area of ​​672 m 2 ·g -1 ;

[0070] The XRD characterization diagram of the customized microporous hard carbon negative electrode material for sodium ion battery prepared in Example 2 of the present invention is as follows: Figure 8 As shown, from Figure 8 It can be found that the structure of the material is an amorphous carbon peak package;

[0071] The half-cell assembled with the sodium ion customized microporous hard carbon negative electrode material prepared in Example 2 of the present invention has a high conductivity at 500 mA·g -1 The cycle performance test diagram at the current density is as follows Fig. 9 shown.

[0072] Example 3

[0073] A method for preparing a customized microporous hard carbon negative electrode material (selenium chloride reactant) comprises the following steps:

[0074] S01. Spread 15g of freeze-dried sodium chloride powder (deposition substrate) in a corundum ark reactor, then place the corundum ark reactor in a plasma enhanced chemical vapor deposition device, introduce selenium chloride and carbon-containing gas for reaction, the amount of selenium chloride used is 15ml, the initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 500°C, the heating rate is 10°C / min, and the reaction time is 60min; after the reaction is completed, remove the heating component of the deposition device, and let the sample cool down quickly to room temperature to obtain an initial sample;

[0075] The carbon-containing gas is a hydrogen mixed gas with a flow rate of 150 sccm and a methane volume content of 30%;

[0076] S02. Take out the initial sample in step S01 into a beaker, and add 50 ml of deionized water to the initial sample to soak for 8 hours; after soaking, filter twice, dry at 50°C in an electric blast drying oven for 10 hours, and then heat in a tubular furnace. The atmosphere of the tubular furnace is nitrogen, the heating time is 60 minutes, the heating temperature is 1000°C, and after cooling, a customized microporous hard carbon negative electrode material is obtained.

[0077] The BET characterization diagram of the customized microporous hard carbon negative electrode material provided in this embodiment 3 is as follows Fig.10 shown; from Fig.10 It can be observed that the customized microporous hard carbon electrode material has micropores of 0.53 nm and a large specific surface area of ​​711 m 2 ·g -1 .

[0078] Example 4

[0079] A method for preparing a customized microporous hard carbon negative electrode material (hydriodic acid reactant) comprises the following steps:

[0080] S01. Spread 15g of freeze-dried sodium chloride powder (deposition substrate) in a corundum ark reactor, then place the corundum ark reactor in a plasma enhanced chemical vapor deposition device, introduce hydroiodic acid and carbon-containing gas for reaction, the amount of hydroiodic acid used is 15ml, the initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 200°C, the heating rate is 10°C / min, and the reaction time is 60min; after the reaction is completed, remove the heating component of the deposition device, and let the sample cool down quickly to room temperature to obtain an initial sample;

[0081] The carbon-containing gas is a hydrogen mixed gas with a flow rate of 150 sccm and a methane volume content of 30%;

[0082] S02. Take out the initial sample in step S01 into a beaker, and add 50 ml of deionized water to the initial sample to soak for 8 hours; after soaking, filter twice, dry at 50°C in an electric blast drying oven for 10 hours, and then heat in a tubular furnace. The atmosphere of the tubular furnace is nitrogen, the heating time is 60 minutes, the heating temperature is 1000°C, and after cooling, a customized microporous hard carbon negative electrode material is obtained.

[0083] The BET characterization diagram of the customized microporous hard carbon negative electrode material provided in this embodiment 4 is as follows Fig.11 shown; from Fig.11 It can be observed that the customized microporous hard carbon negative electrode material has micropores of 0.67 nm and a small specific surface area of ​​297 m 2 ·g -1 .

[0084] Comparative Example 1

[0085] Reference for this comparative example: Zhen, Yichao, et al. "Breaking the limitation of sodium-ion storage for nanostructured carbon anode by engineering desolvation barrier with neat electrolytes." Nano Energy 74 (2020): 104895. A method for preparing a sodium-ion battery storage material with large specific surface area and mesoporous structure, the specific steps are as follows:

[0086] (1) Weigh 45 g of lithium chloride and 55 g of potassium chloride into a beaker and mix them evenly to form a metal chloride salt.

[0087] (2) Weigh 1 g of glucose and 2 g of sodium thiosulfate powder and add them to the metal chloride salt to form a mixture.

[0088] (3) The mixture was placed in a crucible, heated to 350°C at 5°C per minute in an argon atmosphere and kept at that temperature for 2 hours, then heated to 600°C and kept at that temperature for 5 hours, and finally cooled to room temperature to obtain sample A.

[0089] (4) Sample A was crushed into powder, washed with sufficient deionized water and dilute hydrochloric acid, and finally dried at 60° C. for 24 hours to obtain a mesoporous material with a large specific surface area.

[0090] The method of the present invention is compared with Comparative Example 1: The synthesis steps of Comparative Example 1 are cumbersome, and it is necessary to first undergo a molten salt reaction and then anneal for a long time to obtain a carbon material with a large specific surface area. Moreover, the molten salt method used in Comparative Example 1 requires the consumption of a large amount of metal chloride, which is costly, and limits the application of this method to a certain extent. The plasma chemical vapor deposition reaction time used in the method of the present invention is shorter, requires fewer consumables, is lower in cost, is safe and convenient, can be used to quickly prepare customized microporous hard carbon, and has higher universality.

[0091] Compared with the prior art, this application has the following technical effects:

[0092] The customized microporous hard carbon negative electrode material obtained by plasma vapor evaporation deposition and high-temperature heating in the present application has a high specific surface area and rich microporous structure. A large number of microporous structures are conducive to the desolvation of solvated sodium ions during the cycle, which improves the first coulombic efficiency. At the same time, the defects and active sites in the micropores promote the transmission of sodium ions and enhance the rate performance. The sheet structures with high specific surface areas are stacked on each other, which reduces the volume expansion of the material and forms a sodium ion channel with high conductivity. In addition, in terms of process, it is only necessary to change the experimental conditions to customize hard carbon with different specific surface areas and pore sizes. The customization idea is simple and efficient. The preparation method of the present application is simple, low-cost, and can be suitable for large-scale production.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a customized microporous hard carbon negative electrode material, characterized in that: The steps include: S01, laying the deposition substrate flat in the reactor, then placing the reactor in a deposition device, introducing the reactants to react, and cooling to room temperature after the reaction is completed to obtain an initial sample; S02, taking out the initial sample obtained in step S01, adding a solvent to the initial sample for soaking; after the soaking is completed, filtering, drying, heating, and cooling to obtain a customized microporous hard carbon negative electrode material.

2. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S01, the deposition substrate is freeze-dried sodium chloride powder; The amount of the deposition substrate is 10 g to 15 g.

3. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S01, the reactant is at least one of carbon disulfide, phosphorus trichloride, selenium chloride or hydroiodic acid; When the reactant is carbon disulfide, there is no need to add a gas containing carbon elements; When the reactant is at least one of phosphorus trichloride, selenium chloride or hydroiodic acid, a gas containing carbon elements needs to be added; The dosage of the reactant is 10-15 ml.

4. The method for preparing a customized microporous hard carbon negative electrode material according to claim 3, characterized in that: The carbon-containing gas is a hydrogen mixed gas with a methane volume content of 30%, and a flow rate of 50 sccm to 150 sccm.

5. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S01, the reactor is a corundum ark; and the deposition device is a plasma enhanced chemical vapor deposition device.

6. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S01, the initial temperature of the reaction is 20°C to 50°C, the reaction temperature of the reaction is 20°C to 500°C, the heating rate is 10°C / min; the reaction time is 30min to 60min; The cooling method is to remove the heating component of the deposition device after the reaction is completed, so that the sample can be quickly cooled down to room temperature.

7. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S02, the solvent is deionized water, and the amount of the solvent is 50ml to 100ml; The soaking time is 8h to 12h.

8. The method for preparing a customized microporous hard carbon negative electrode material according to claim 1, characterized in that: In step S02, the filtration is performed once to twice; The drying temperature is 50°C to 100°C, and the drying time is 10h to 12h; The heating device for heating is a tubular furnace; The heating temperature is 900° C. to 1000° C., the heating time is 30 min to 90 min, and the heating atmosphere is nitrogen.

9. A customized microporous hard carbon negative electrode material is obtained by the preparation method described in any one of claims 1 to 8.

10. The customized microporous hard carbon negative electrode material according to claim 9 is used in sodium ion batteries.

Citation Information

Patent Citations

  • High-capacity rapid charging and discharging graphene and hard carbon composite material, preparation method thereof and application of composite material in sodium-ion battery

    CN114156456A

  • Hard carbon-inorganic lithium salt composite electrode material and preparation method and application thereof

    CN114497506A

  • Negative electrode material and preparation method and application thereof

    CN116960291A

  • Non-metal doped oxygen reduction catalyst as well as preparation method and application thereof

    CN118281246A

  • Metal-Sulfur Battery Cathode Containing Humic Acid-Derived Conductive Foam Impregnated with Sulfur or Sulfide

    US20180083289A1